A Study on the Durability of Dispersive Soils Improved by Alum in Western Jilin Province of China. (31st August 2021) - Yuan, Xiaoqing; Wang, Xi; Chen, Hui'e; Shi, Zhiyong; Shi, Bin; Niu, Cencen
Abstract : Dispersive soil, which has the characteristics of low erosion resistance and high dispersibility in water, is the main reason for the channel slope failure that happened in the planning area of the Western Alkaline Treatment project in Jilin Province. Therefore, the study focused on the improvement of dispersive soil. In this research, pinhole test and crumb test were conducted on the soil under varying percentages of alum (1%, 1.5%, 2%, 2.5%, and 3%). Results indicated that alum can reduce the dispersivity of soil distinctly, and the optimal content of alum was 2.5%. This research also investigated the durability of 2.5%-alum-improved dispersive soil for dispersibility under the condition of freeze-thaw cycle. The soil samples with 2.5% alum content were subjected to pinhole test, crumb test, double hydrometer test, and percentage of exchangeable sodium ion test under the different number of freeze-thaw cycles. The results showed that the 2.5%-alum-improved soil was unaffected by the number of freeze-thaw cycles, which illustrated that alum can be used to improve soil dispersivity in engineering practice.